Baicalin enhances antioxidant, inflammatory defense, and microbial diversity of yellow catfish (Pelteobagrus fulvidraco) infected with Aeromonas hydrophila - Yan, Pupu; Liu, Jiali; Huang, Yongxi; Yi, Tilin; Zhang, Heng; Dai, Gang; Wang, Xiong; Gao, Zhenzhen; He, Bin; Guo, Weili; Su, Yingbing; Guo, Liwei (Frontiers in Microbiology, 2024)
The aim of this research was to clarify the mechanism through which baicalin exerts its inhibitory effects on Aeromonas hydrophila infection. The antibacterial efficacy of baicalin was assessed by determining its minimum inhibitory concentration (MIC) against A. hydrophila. Various parameters, including the growth curve, cell wall integrity, biofilm formation, AKP content, and morphological alterations of A. hydrophila, were analyzed. In vivo experiments involved the administration of A. hydrophila 4 h post-intraperitoneal injection of varying doses of baicalin to induce infection, with subsequent monitoring of mortality rates. After a 3 d period, liver, spleen, and intestinal tissues were harvested to evaluate organ indices, antioxidant and immune parameters, as well as intestinal microbial composition. The findings indicated that baicalin treatment resulted in the disruption of the cell wall of A. hydrophila, leading to the loss of its normal structural integrity. Furthermore, baicalin significantly inhibited biofilm formation and facilitated the release of intracellular proteins (P<0.05). In vivo, baicalin enhanced the survival rates of yellow catfish infected with A. hydrophila. Compared to the control group, the liver index of yellow catfish was elevated, while the spleen and intestinal indices were reduced in the baicalin-treated group (P<0.05). Additionally, baicalin at an appropriate dosage was found to increase levels of SOD, GSH, CAT, ACP, and AKP in yellow catfish (P<0.05), while simultaneously decreasing MDA accumulation and the mRNA expression of inflammatory markers such as Keap1, IL1, IFN-γ and TNF-α, (P<0.05). Moreover, baicalin significantly enhanced the operational taxonomic unit (OTU) count in A. hydrophila-infected yellow catfish (P<0.05), restoring the abundance of Barnesiellaceae, Enterobacteriaceae, Plesiomonas, and UBA1819 (P<0.05). In summary, baicalin demonstrates the potential to improve the survival rate of yellow catfish subjected to A. hydrophila infection, augment antioxidant and immune responses, mitigate inflammation, and enhance intestinal microbial diversity.